Functional traits and performance of tree species in a Mixed Ombrophilous Forest in the “Planalto Sul Catarinense” region - Schlickmann, Monique Bohora (2019)
We aimed to describe the functional traits of the tree species of a Mixed Ombrophilous Forest fragment in the “Planalto Sul-Catarinense” region and to test if function traits predict tree species demographic rates. For the most abundant species, we determined the functional traits - leaf area (AF), specific leaf area (AFE), wood basic density (DM) and maximum potential height (Hmax) – and demographic rates – mortality, recruitment, gain and loss of basal area, turnover and net changes. We analyzed the data through Principal Component Analysis (PCA) and Generalized Least Square (GLS) models. The data showed that the species have a high functional heterogeneity, mainly in relation to Hmax, AFE (PCA - Axis 1), and DM (PCA - Axis 2).  Demographic rates were only affected by Hmax and AFE. We concluded that (i) the variation of species functional traits synthesized a spectra of ecological strategies related to the distribution of species along forest vertical profile and in areas with different times post-disturbance; and that (ii) the demographic rates of the species were predicted by the functional traits that indicated species ability to colonize the forest understory.